Growth and Survival Rate of Tilapia (Oreochromis niloticus) Given Acanthaster planci Based Feed - safir, muhammad; Mansyur, Kasim; Serdiati, Novalina; Mangitung, Septina F; Tamrin, Fachri Ramadhan (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Crown of thorns star (Acanthaster planci) is one of the aquatic organisms that contains protein and amino acids similar to fish meal, and has not been used properly for feed ingredients. This research was conducted to examine A planci flour as a feed ingredient on the growth of tilapia. The research method was a completely randomized design, consisting of 4 treatments with doses of A planci flour, 7 %, 14 %, 21 % and 0 % (control), given three replications. The results showed growth (daily growth rate and biomass increase) of 3.84 %, 3.81 %, 4.00 %, and 4.21 % per day, and 61.00 g, 49.33 g, 54.33 g, and 52.67 g. This growth did not show any difference between treatments (P>0.05). Feed consumption ranged from 129.20 g â€“ 132.24 g (P>0.05). Feed conversion ratio and survival rates ranged from 2.13 â€“ 2.75 and 94.44 % - 100.00 % (P>0.05). A. planci flour can be used up to 21 % as a source of protein for feed ingredients in minimizing fish meal as feed ingredients.Â